Comparative study on the behaviour of normalweight concrete and lightweight concrete using 0.50 and 0.70 water (cement ratio) / Noor Azhar Mohd Nor - Mohd Nor, Noor Azhar (1998)
For structural applications of lightweight Concrete (LWC), the density of concrete is often more important than the strength. A decreased density for the same strength level permits a saving in dead load for structural design and foundation. The aim is to study the comparison on the behaviour ofNWC (normalweight concrete) and LIVC (light weight concrete). The concrete is of grade 35 and the water/cement ratio are at 0.50 and 0.70. The strength development at test will be carried out on 150 mm x 150 mm x 150 mm cube at 3, 7, 14 and 28 days. It is meant to study which portion of water/cement ratio gives the best output for lightweight aggregate concrete. Conclusively, the 0.5 w/c ratio of 60% LECA replacement gives better overall output as compared to 0.70 w/c ratio. Unfortunately, no conclusion can be outlined to evaluate which is better between LWC and NWC of the same water/cement